2003
DOI: 10.3109/01674820309074689
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported crying during the menstrual cycle: Sign of discomfort and emotional turmoilor erroneous beliefs?

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research -You may not further distribute the material or use it for any profit-making activity or commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…From the age of 11, however, differences in crying proneness and frequency begin to emerge (van Tilburg et al, 2002). Of course, contrary to the notion that women might be biologically inclined to be more emotional, research investigating the role of menarche and crying have found no association with menstrual cycles and crying behaviors (van Tilburg et al, 2003; Romans et al, 2017). Furthermore, much of this change appears to stem from a reduction in boys’ expressions of crying, rather than an increase in girls’.…”
mentioning
confidence: 82%
“…From the age of 11, however, differences in crying proneness and frequency begin to emerge (van Tilburg et al, 2002). Of course, contrary to the notion that women might be biologically inclined to be more emotional, research investigating the role of menarche and crying have found no association with menstrual cycles and crying behaviors (van Tilburg et al, 2003; Romans et al, 2017). Furthermore, much of this change appears to stem from a reduction in boys’ expressions of crying, rather than an increase in girls’.…”
mentioning
confidence: 82%
“…First, this study relied upon self-reports of crying. Although the ACI-S has demonstrated validity and the use of self-reports of crying has been shown to be valid in many contexts, it is also known that retrospective self-reports can be vulnerable to bias due to implicit theories or memory failures [van Tilburg et al, 2003]. Thus, it becomes imperative for future work to use a variety of different measures to index crying in mood disorders, including on-line measures of crying using experience sampling or daily diary methodologies, as well as designs that incorporate observational data and data from other informants.…”
Section: Discussionmentioning
confidence: 99%
“…A first limitation is that crying was assessed entirely by self-reports. Although the used frequency measures and the Crying Proneness Scale (Denckla et al, 2014) have demonstrated validity, it is also known that retrospective self-reports can be vulnerable to bias due to implicit theories or memory failures (Van Tilburg et al, 2003). Thus, in future research, the current findings need to be crossvalidated with observations and other methodology to assess crying, such as exposing patients and controls to emotional movies (Van der Veen et al, 2012) or using daily diary measures of crying (Bylsma et al, 2011).…”
Section: Limitations and Future Researchmentioning
confidence: 99%